Microwaves disinfection of farmland. Issue 16 (1st November 2016) - Spanu, Michele; Fanti, Alessandro; Bruno Lodi, Matteo; Casu, Sergio; Desogus, Francesco; Bisceglia, Bruno; Mazzarella, Giuseppe
Abstract: This work focuses on the heat transfer dynamics in agricultural soils when exposed to microwave fields, in order to disinfect them and to eliminate dangerous organisms without using pesticides. The work manages with the use of a horn antenna to irradiate the superficial layer of soils and so to eliminate harmful bio-agents within a fixed depth. The soil was approximated using a transmission line model. Considering the dielectric constant of the ground as a function of the soil water content, it was possible to evaluate the power absorbed by the irradiated ground and the temperature increase and its profile depending on the irradiation time. Since the latter information is strictly connected to the heat transfer process occurring in the system, we demonstrated the feasibility of the methodology here proposed to achieve difficult conditions for microbial and pathogens life, leading to an effective disinfection of the treated farmland.